Syndecan-1: A Review on Its Role in Heart Failure and Chronic Liver Disease Patients’ Assessment - Radu-Stefan Miftode; Ionela-Lăcrămioara Şerban; Amalia-Stefana Timpau; Ionela-Larisa Miftode; Adriana Ion; Ana-Maria Buburuz; Alexandru-Dan Costache; Irina-Iuliana Costache (Cardiology Research and Practice)
The close connection and interaction between the cardiac and the liver functions are well-known, as cirrhotic cardiomyopathy is an important clinical entity which best describes the mutual pathogenical influence between these two organs. Due to the fact that cardiac dysfunction in patients with chronic hepatic disorders is oligosymptomatic or even asymptomatic, an early diagnosis represents a challenge for every physician. Syndecan-1—a transmembrane proteoglycan that exerts its functions mainly via its heparane sulfate chains—is a very promising biomarker, correlated not only with the degree of cardiac fibrosis but also with the severity of liver fibrosis. Many studies highlighted its role in the development of cardiac fibrosis or atherogenesis, being significantly correlated with the activity of angiotensin II. Multiple evidence revealed that syndecan-1 is also associated with tissue injury and may regulate inflammatory and regenerative responses, being considered a protective molecule that limits the inflammation and reduces cardiac remodelling and dysfunction after a myocardial infarction. Syndecan-1 may also be used as a reliable biomarker for the noninvasive assessment of liver fibrosis. Under various fibrogenetic conditions, shedding of syndecan’s extracellular domain took place, becoming a soluble form that binds different growth factors and inhibits further fibrosis. This complex molecule is also involved in the lipid metabolism, by altering the clearance of cholesterol particles, and in chronic hepatitis, by enhancing the viral invasion of hepatocytes. Due to the growing interest in this biomarker, multiple studies aimed at revealing syndecan-1’s potential benefits in the diagnosis and prognosis assessment in patients with heart failure or chronic liver disorders. In this review, we review the mechanisms by which syndecan-1 exerts its effects and the possible perspectives opened by its use as a dual cardio-hepatic biomarker.